2014
DOI: 10.1177/0267659114548256
|View full text |Cite
|
Sign up to set email alerts
|

The impact of haemodilution and bypass pump flow on cerebral oxygen desaturation during cardiopulmonary bypass - A comparison of two systems of cardiopulmonary bypass

Abstract: The average indexed bypass pump flow was significantly lower with Mini-CPB. When combined with haemoglobin concentration, the average oxygen delivery was the same between groups. Patients in the C-CPB group had a greater duration and severity of cerebral desaturation to a level <20% below baseline values, but none reached the depth and duration of the cerebral desaturation associated with poor outcome. Cerebral oxygen desaturation with C-CPB was significantly associated with low flows during bypass, whereas de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(19 reference statements)
0
2
1
1
Order By: Relevance
“…A previous meta-analysis demonstrated a significant reduction in the incidence of stroke between the MCPB and CCPB groups[ 9 ] and the MCPB has been previously shown to have improved cerebral perfusion and reduced overall inflammation as compared to CCPB with neurocognitive outcomes. [ 16 17 18 ] However, we found that there was no significant difference for POCD between the two groups. This could be due to a number of reasons.…”
Section: Discussioncontrasting
confidence: 52%
“…A previous meta-analysis demonstrated a significant reduction in the incidence of stroke between the MCPB and CCPB groups[ 9 ] and the MCPB has been previously shown to have improved cerebral perfusion and reduced overall inflammation as compared to CCPB with neurocognitive outcomes. [ 16 17 18 ] However, we found that there was no significant difference for POCD between the two groups. This could be due to a number of reasons.…”
Section: Discussioncontrasting
confidence: 52%
“…Bennett and his colleagues came to the conclusion that in conventional CPB, the reason for cerebral desaturation was the failure to achieve the target of the blood flow rate. [10] In the same study, when using mini-CPB, the most important parameter was the haemoglobin concentration. Furthermore, a major complication that is associated with cerebral hypoperfusion is the postoperative cognitive decline (POCD) after CPB.…”
Section: Blood Flow During Cpb: Goals and Requirementsmentioning
confidence: 95%
“…Nowadays, NIRS is widely used as a monitoring in surgical patients. It is used during cardiopulmonary bypass to monitor cerebral circulation [ 23 ]. It was also used to monitor the effect of hypotension induced by anesthesia induction [ 24 ] and the effects of different vasopressors used to correct this hypotension on brain circulation [ 24 , 25 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%